2020
DOI: 10.1080/17482631.2020.1857550
|View full text |Cite
|
Sign up to set email alerts
|

Understanding empowerment for a healthy dietary intake during pregnancy

Abstract: Purpose : In order for health professionals to encourage pregnant women with a low socioeconomic status (SES) to move towards empowerment for a healthy dietary intake, crucial steps are to understand the perspectives of pregnant women of food and eating and to identify opportunities for empowerment. This study aimed to examine the perspectives of pregnant women on food and eating and to identify the opportunities for empowerment towards a healthy dietary intake. Methods : Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…This study showed that low SES pregnant women are motivated to eat healthy and that they are satisfied with their dietary intake, which has also been found in previous studies [ 9 , 10 , 27 ]. In addition, many of the pregnant women in this study said they were happy with how healthy their dietary intake was and stressed that they did not feel the need to have a perfect score for healthy eating.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study showed that low SES pregnant women are motivated to eat healthy and that they are satisfied with their dietary intake, which has also been found in previous studies [ 9 , 10 , 27 ]. In addition, many of the pregnant women in this study said they were happy with how healthy their dietary intake was and stressed that they did not feel the need to have a perfect score for healthy eating.…”
Section: Discussionsupporting
confidence: 88%
“…low SES pregnant women, midwives, dietitians, gynaecologists and other health professionals), thereby ensuring that the strategy closely matches the needs, interests and capacities of the different stakeholders involved [ 23 , 24 ]. The first phase of the study was directed at exploring the perspectives of the target group, low SES pregnant women, on food and eating during pregnancy and at understanding the opportunities for empowerment as experienced by these women [ 10 ]. This study is part of the second phase of the research project which is focused on the professionals in antenatal care and the opportunities that they identify for improving the dietary intake of low SES pregnant women.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inadequate diet has been documented as an association with poor maternal outcomes (increased risk of preeclampsia, gestational diabetes and extreme gestational weight gain), negative birth outcomes (premature and low birth weight), and childhood and adult health outcomes (obesity and chronic heart disease) [ 10 , 11 ]. Pregnant women with a low socioeconomic status faced an additional challenge to maintaining a healthy diet due to a lack of money, information and skills to make nutritional modifications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%